Comparison of Psychological and Physiological Changes of the Anxiety in Various Sports - Kagan, Sertan; Koruc, Ziya; latifoglu, Gozde (Editura Lumen, Iasi, 2017)
The aim of this study is to determine a more convenient physiological measurement instead of HR (the physiological indicators of competition anxiety). STAI, CSAI-2 and ProComp+Biofeedback were used before and after the competition (N=38). Data were analyzed with repeated measure ANOVA and Multiple Linear Regression. Non-significant difference was found between the results of HR, EMG, skin transmission, EEG, state anxiety and self confidence before and after the competition. Significant difference was found between the respiration, skin temperature, cognitive, somatic and trait anxiety before and after the competition. The post competitive variables are significant predictors of post competitive cognitive and somatic anxiety. As a result respiration, skin temperature measurements and questionnaires can be used instead of Heart Rate.
Keywords: heart rate; competitive state anxiety; biofeedback; EEG; EMG; respiration